2018
DOI: 10.1021/acs.jpcc.8b02937
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of NLO Properties in OBO Fluorophores Derived from Carbazole–Coumarin Chalcones Containing Carboxylic Acid at the N-Alykl Terminal End

Abstract: The nonlinear optical (NLO) properties of carbazole–coumarin-based chalcones and their OBO complexes of D−π–A and D−π–A−π–D types with carbazole as donor substituted with N-alykl chain at the 9 position with carboxylic acid end group are studied in detail. These dyes exhibit good emission solvatochromism. The NLO properties of dyes 5–8 were studied by two methods, namely, solvatochromic and computational method. The linear polarizability (α), hyperpolarizability (β), and second-order hyperpolarizability (γ) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 61 publications
(28 citation statements)
references
References 57 publications
0
28
0
Order By: Relevance
“…LiNbO 3 and KTiPO 4 ) 2 were widely used in commercial nonlinear optical (NLO) devices, NLO materials gained enormous attention and became an active research eld, owing to their broad applications. [3][4][5][6][7][8][9] Up to now, various types of strategies have been proposed to enhance (hyper)polarizability coefficients, i.e., designing organic molecules with a donor-acceptor architecture, 10,11 spin-polarization molecules with singlet diradical character, [12][13][14] importing diffuse excess electrons into a molecular system to form excess electron compounds, etc. Excess electron compounds have been proven to serve as potential candidates for NLO materials with excellent NLO responses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…LiNbO 3 and KTiPO 4 ) 2 were widely used in commercial nonlinear optical (NLO) devices, NLO materials gained enormous attention and became an active research eld, owing to their broad applications. [3][4][5][6][7][8][9] Up to now, various types of strategies have been proposed to enhance (hyper)polarizability coefficients, i.e., designing organic molecules with a donor-acceptor architecture, 10,11 spin-polarization molecules with singlet diradical character, [12][13][14] importing diffuse excess electrons into a molecular system to form excess electron compounds, etc. Excess electron compounds have been proven to serve as potential candidates for NLO materials with excellent NLO responses.…”
Section: Introductionmentioning
confidence: 99%
“…57 On the other hand, NLO switches with a large difference in NLO properties in the presence of external stimulator triggering have attracted more and more attention in recent years, 19,20,50 because of their excellent potential applications in signal processing, data storage and optical frequency converters etc. [3][4][5][6][7][8][9] In the presence of EEF triggering, NLO switches of the organic electride molecule K(1)/calix [4]pyrrole/K(2) with b e 0 values ranging from 0 (EEF ¼ 0 (a.u.)) to 3.147 Â 10 6 (a.u.)…”
Section: Introductionmentioning
confidence: 99%
“…The theoretically observed values of first‐order hyperpolarizability (β) and second‐order hyperpolarizability (γ) for 2‐napthol azo dyes 1–4 are larger than the values for hyperpolarizability of urea . Moreover, the β and γ values of these dyes were compared with the reported donor‐π‐acceptor dyes . We found that β and γ values of these dyes are competes with the reported donor‐π‐acceptor dyes supplementary information (Table S30).…”
Section: Resultsmentioning
confidence: 83%
“…Patil et al., reported the NLO properties of D‐π‐A based 1‐(4‐bromophenyl)‐3‐(2, 4, 5‐trimethoxyphenyl) prop‐2‐en‐1‐one (2, 4, 5‐TMBC) by experimental method, later this experimental NLO properties explored theoretically by Muhammad et al . Recently, the NLO properties of D‐π‐A based coumarin‐chalcone studied experimental method and correlated theoretically by our research group …”
Section: Introductionmentioning
confidence: 77%
“…The coumarin derivatives are widely used in laser dyes, organic light emitting diodes (OLED), dyes sensitized solar cells (DSSC), cell‐imaging and optical brighteners . In recent years, the coumarin‐chalcone chromophores are widely studied for their NLOphoric properties . Coumarin‐chalcone shows solid‐state photoluminescence, AIE, second harmonic generation (SHG) properties, the high sensitivity of transition energy to the static electric field changes, good ICT in D‐π‐A .…”
Section: Introductionmentioning
confidence: 99%